2010
DOI: 10.1176/ps.2010.61.7.698
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Housing Status With Substance Abuse Treatment and Service Use Outcomes Among Veterans

Abstract: Homelessness affects substance abuse treatment outcomes and costs. Interventions are needed to reduce homelessness among veterans entering substance abuse treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…One study found that 22.8% of ED patients with high-risk substance use were homeless, but no comparison was given for patients without high-risk use (Hankin et al, 2013). Our findings are consistent with research conducted in other groups including primary care patients, and Veterans and others entering substance use treatment (Buchholz et al, 2010; Eyrich-Garg et al, 2008; Krupski et al, 2015; Welte and Barnes, 1992). …”
Section: Discussionsupporting
confidence: 90%
“…One study found that 22.8% of ED patients with high-risk substance use were homeless, but no comparison was given for patients without high-risk use (Hankin et al, 2013). Our findings are consistent with research conducted in other groups including primary care patients, and Veterans and others entering substance use treatment (Buchholz et al, 2010; Eyrich-Garg et al, 2008; Krupski et al, 2015; Welte and Barnes, 1992). …”
Section: Discussionsupporting
confidence: 90%
“…Homelessness is a costly problem, partly as a result of the associated increased health care costs, particularly among those with substance use disorders. 4850 Our findings suggest that, if eligible for Medicaid coverage, homeless adults are just as likely as the housed to enroll, which will likely increase their odds of entering treatment, ultimately improving their health status and reducing costs to society.…”
Section: Discussionmentioning
confidence: 91%
“…Unstable housing and homelessness are associated with greater substance use severity (Eyrich-Garg, Cacciola, Carise, Lynch, & McLellan, 2008) and higher service utilization costs (Buchholz et al, 2010), and a substantial number of those in substance abuse treatment are affected. Among a sample of 5,629 treatment-seekers at 158 substance abuse treatment programs across the US, 12% were homeless and an additional 20% were marginally housed and at risk for homelessness (Eyrich-Garg et al, 2008).…”
Section: Introductionmentioning
confidence: 99%